2013
DOI: 10.1186/cc12575
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet therapy and the outcome of subjects with intracranial injury: the Italian SIMEU study

Abstract: IntroductionPre-injury antithrombotic therapy might influence the outcome of subjects with head injuries and positive computed tomography (CT) scans. We aimed to determine the potential risk of pre-injury antiplatelet drug use on short- and long-term outcome of head injured subjects admitted to emergency departments (EDs) in Italy for extended observation.MethodsA total of 1,558 adult subjects with mild, moderate and severe head injury admitted to Italian EDs were studied. In multivariable logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 38 publications
0
58
1
Order By: Relevance
“…The use of antithrombotic agents leading to subsequent impairment of the hemostatic system in patients suffering from TBI, pICH and pSAH is known to be one of the most relevant risk factors for early neurological deterioration, hematoma growth, need for neurosurgical intervention, unfavorable neurological outcome and increased mortality [11,12,15,17,19,25]. Although in univariable analysis a pathological Multiplate result was associated with unfavorable outcome, this association did not persist when multivariable analysis was performed.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The use of antithrombotic agents leading to subsequent impairment of the hemostatic system in patients suffering from TBI, pICH and pSAH is known to be one of the most relevant risk factors for early neurological deterioration, hematoma growth, need for neurosurgical intervention, unfavorable neurological outcome and increased mortality [11,12,15,17,19,25]. Although in univariable analysis a pathological Multiplate result was associated with unfavorable outcome, this association did not persist when multivariable analysis was performed.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, over the last decades TBI has increasingly been recognized not only as the leading cause of mortality among patients under 45 years of age, but also as a growing disease in the aging population of industrialized countries, underscoring the immense socioeconomic impact of acute brain injury. While of course antiplatelet medication significantly reduces ischemic cardiovascular and cerebrovascular events [21], an impaired platelet function in the case of intracranial trauma and/or acute bleeding has been shown to significantly increase the risk for hematoma progression with subsequent neurological deterioration and increased mortality rates [11,17,19,26]. Thus, it has been suggested that clinicians should always consider and be aware of this increased risk profile when treating respective patients [4].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Antiplatelet medication was identified as the most important risk factor for re-bleeding after neurosurgical procedures [49] and it is associated with an increased risk of morbidity and mortality after TBI and spontaneous intracranial haemorrhage [50,51]. The degree of platelet inhibition through intake of antiplatelet medication varies considerably among individuals and depends on several factors such as genetic profile and patient compliance.…”
Section: Antiplatelet Medication and Bleeding Risksmentioning
confidence: 99%